Is CPAP the Key to Reduce the Cardiovascular Risk in Patients with OSA? - Kiran Abraham-Aggarwal; Ashutosh Kacker (International Archives of Otorhinolaryngology)
Introduction Obstructive sleep apnea (OSA) is a prevalent condition often managed with continuous positive airway pressure (CPAP) treatment. There is an ongoing debate about the link between OSA and cardiovascular disease (CVD), but the existing evidence points toward an association.